Strengthening the state defense and building an attitude of nationalism by implementing the universe war strategy in the era of globalization - Mohammad Iqbal Dwi Prasetyo; Priyanto Priyanto; I Wayan Midhio (Universitas Pertahanan Republik Indonesia (UNHAN RI), 2022)
Defending the State in a broad sense is not only in dealing with the military but also non-military threats. In the era of globalization and the rapid progress of science and technology, the forms of threats are very varied and complex; only nations that have competitive advantages can compete and win this competition. So that this research is intended to find out more about how defending the country awakens an attitude of nationalism, and the Universal War Strategy can be implemented in dealing with one form of war in the globalization era. The method used in this study is to use a phenomenological qualitative descriptive method, where the researcher will apply and apply his subjectivity and interpersonal skills in the process of exploratory research. The researchers assess that there is a correlation between state defense and nationalism with the implementation of a universal war strategy with efforts to deal with the war in the era of globalization, which must be spelled out more specifically in terms of the application of universality to improve the character of the nation, especially the younger generation to increase further their sense of nationalism towards the State of Indonesia because they are candidates for continuing the nation's struggle and development in the future.